NATO and the Challenges of Austerity - Larrabee, F. Stephen (RAND Corporation, 2012)
In the coming decade, NATO faces growing fiscal austerity and declining defense budgets. This study analyzes the impact of planned defense budget cuts on the capabilities of seven European members of NATO: the United Kingdom, France, Germany, Italy, Spain, the Netherlands, and Poland. The authors assess the implications of the cuts for NATO capabilities and strategy and for U.S. policy.